The looks and thoughts of great thinkers of East – Confucius and А bay in written works “Lun Yu” and “Thinking” - Abdraimova, N. B.; Ibraimova, A. R. (Journal of Oriental Studies, 2016)
The looks and thoughts of great thinkers of East – Confucius and Аbay are reviewed in the research. Great thinkers called people to the justice, education, humanity.